Supply Chain Risk Mitigation Strategies, Methods and Applications - Khojasteh, Yacob; Xu, Henry; Zolfaghari, Saeed (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book covers central issues in mitigating supply chain risks from various perspectives. Today's supply chains are vulnerable to disruptions that can have a significant impact on firms, business and performance. The aim of supply chain risk management is to identify the potential sources of risks and implement appropriate actions in order to mitigate supply chain disruptions. In this regard, the book presents a wealth of methods, strategies and analyses that are essential for mitigating supply chain risks. As a comprehensive collection of the latest research and cutting-edge developments in supply chain risk and its mitigation, the book is structured into four main parts, addressing supply chain risk strategies and developments; supply chain risk management review; supply chain sustainability and resilience; and supply chain analysis and risk management applications. The contributing authors are leading academic researchers and practitioners, who combine findings and research results with a practical and contemporary view on how companies can best manage supply chain risks and disruptions, as well as how to create resilient and sustainable supply chains. This book can be used as an essential resource for students and scholars who are interested in pursuing research or teaching courses on the rapidly growing field of supply chain management. It also offers an interesting and informative read for managers and practitioners who need to deepen their understanding of effective supply chain risk management.
Part I: Review on Supply Chain Risk Management -- Risks in Supply Chain Management -- Supply Chain Risk Management: An Enterprise View and a Survey of Methods -- Part II: Supply Chain Risk Strategies and Developments -- Retail Supply Chain Risk and Disruption: A Behavioral Agency Approach -- Mitigation of Supply Chain Vulnerability Through Collaborative Planning, Forecasting, and Replenishment (CPFR) -- The Boom and Bust of Medical Supplies During the COVID-19 Pandemic -- Part III: Supply Chain Sustainability and Resilience -- Sustainability Practices for Enhancing Supply Chain Resilience -- A Theoretical Framework for Supply Chain Resilience Planning -- Toward a Resilient Supply Chain -- Integrated Optimization of Resilient Supply Chain Network Design and Operations Under Disruption Risks -- Balancing Sustainability Risks and Low Cost in Global Sourcing -- Part IV: Supply Chain Analysis and Risk Management Applications -- A Bi-objective, Risk-Aversion Optimization Model and Its Application in a Biofuel Supply Chain -- Conceptualizing and Modeling Supply Chains in the Hazard Context -- Developing Predictive Risk Analytic Processes in a Rescue Department -- A Manufacturing-Supply Chain Risk Under Tariffs Impact in a Local Market.
Keywords: Business logistics; Production management; Operations research; Management science; Industrial engineering; Production engineering; Mathematical optimization; Supply Chain Management; Operations Management; Operations Research, Management Science .; Industrial and Production Engineering; Optimization